A Comparative Study of Three Measurement Methods of Chinese Character Recognition for L2 Chinese Learners - Zhang, Haiwei; Kim, Sun-A.; Zhang, Xueyan (Frontiers in Psychology, 2022)
Measuring Chinese character recognition ability is essential in research on character learning by learners of Chinese as a second language (CSL). Three methods are typically used to evaluate character recognition competence by investigating the following properties of a given character: (a) pronunciation (phonological method), (b) meaning (semantic method), and (c) pronunciation and meaning (phonological & semantic or PS method). However, no study has explored the similar or dissimilar outcomes that these three measurements might yield. The current study examined this issue by testing 162 CSL learners with various L1 backgrounds and Chinese proficiency levels. Participants’ performances in character recognition measured using a phonological method, a semantic method, and a PS method were compared, which led to two major findings. In terms of similarity, participants’ performances in character recognition and the influence of L1 background and Chinese proficiency level on character recognition was similar across the three methods. As for differences, the semantic method could yield a character recognition test with better quality than the other two methods, and the three methods yielded different best fitting models and showed different prediction for Chinese proficiency across different L1 groups. Theoretical and practical implications of these findings are proposed.